2020
DOI: 10.3390/jcm9041182
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Sensory Screening in Anorexia Nervosa and Associations with Autistic Traits

Abstract: Background: Research suggests that people with anorexia nervosa (AN) experience subjective hypersensitivity to external sensations that may require consideration in treatment. These difficulties may be particularly pronounced in people with AN and high autistic traits. The purpose of this pilot study was to explore the use of a brief screening tool to assess sensory sensitivity in individuals receiving treatment for AN, and to assess if self-rated sensitivity in AN is related to autistic traits. Methods: 47 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…For example, research demonstrates that people with EDs avoid new sensory experiences. Kinnaird and colleagues demonstrated that patients with EDs, with and without autism spectrum comorbidity, are hypersensitive to smells, touch and noise, and hypersensitivity in different domains could be addressed in their treatment [ 4 6 ]. Clinical audit data shows that almost 37% of people with AN treated in inpatient and day-care programmes have high Autism Spectrum Condition (ASC) traits and are therefore likely to experience some sensory differences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research demonstrates that people with EDs avoid new sensory experiences. Kinnaird and colleagues demonstrated that patients with EDs, with and without autism spectrum comorbidity, are hypersensitive to smells, touch and noise, and hypersensitivity in different domains could be addressed in their treatment [ 4 6 ]. Clinical audit data shows that almost 37% of people with AN treated in inpatient and day-care programmes have high Autism Spectrum Condition (ASC) traits and are therefore likely to experience some sensory differences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that patients with no autistic traits as well as high autistic traits benefited from the sensory changes made in the dining room evidenced with focus groups [ 9 ]. Based on the research evidence [ 4 , 10 ], we have developed one-off workshops which offer both psychoeducational content and experiential activities to support patients by creating a soothing and helpful sensory toolkit.…”
Section: Introductionmentioning
confidence: 99%
“…To address this important health issue, the current Special Issue collected 21 articles examining the most recent and relevant scientific findings regarding advances in ED. The published articles comprised three reviews and 18 research articles focusing on different aspects, such as genetic [ 7 ] and epigenetic factors [ 8 ], biomarkers [ 9 ], comorbidity [ 10 , 11 , 12 , 13 , 14 ], clinical phenotypes [ 15 , 16 ], neurocognition [ 12 , 17 , 18 , 19 , 20 , 21 ], treatment predictors [ 22 ], and treatment models and therapeutic targets [ 19 , 23 , 24 , 25 , 26 , 27 ]. Altogether, these studies may provide increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.…”
mentioning
confidence: 99%
“…Therefore, Kerr-Gaffney et al [ 13 ] compared the emotion recognition abilities and attention to faces using eye-tracking in patients with AN and healthy control, concluding that difficulties in emotion recognition appear to be associated with high comorbid autistic traits rather than with a phenotypic feature of AN, independent of illness state. In the same vein, Kinnaird et al [ 14 ] explored the use of a brief sensory sensitivity screener in patients with AN, to assess whether self-rated sensory sensitivity is related to autistic traits. The results of this study showed that patients with AN and high autistic traits scored themselves as more sensitive in the areas of smell, vision, texture, and overall total screening scores, compared to those with low autistic traits.…”
mentioning
confidence: 99%
See 1 more Smart Citation